Financial Awards and Their Effect on Football Players’ Anxiety and Coping Skills - Kaplánová, Adriana (Frontiers in Psychology, 2020)
Financial awards can be an important factor affecting athletes´mental preparation and various skills to manage stress. Since such a link has not yet been studied, the study has been designed to evaluate the moderation effect of financial awards in relation to football players´anxiety and coping skills. The study consist of 110 male football players aged 18 to 32 who were divided into two groups: financial awarded (n = 48) and financial unawarded for sports performance (n = 62). The anxiety of football players was measured by Sport Anxiety Scale SAS-2. Coping strategies to manage stress were assessed by Athletic Coping Skills Inventory ACSI-28. The effect of financial awards in relation to football players´anxiety and coping skills was evaluated by the mediators model using the PROCESS software. The results suggest that financial awards are important factors influence football players´anxiety and coping skills. Financial awards increase the motivation of football players to better prepare for sports performance, which has been proven, through better setting of performance goals and more careful mental preparation. Financial awarded football players seem to respect the coach and follow his instructions to greater extent than unawarded football players, which may be due to the financial benefits and the commitment they have confirmed by signing to the football club. In another aspect, the financial awards are likely to increase the cognitive trait of the anxiety of football players. It seems that financial players are more concerned about the failure of the match, which increases their anxiety, especially it is cognitive part, and affects their sports performance. For this reason, we encourage sports organizations to focus more on the mental preparation of football players. It is important to provide football players the opportunity to graduate short or long-term mental training conducted by a trained sports psychologist not only at the time of the athlete's failure but also as a preventive measure against increasing cognitive anxiety. We recommend sports organizations to train coaches in the field of mental training, preferably through annual short training sessions with a sports psychologist and also through it to influence the development of desirable athletes´coping skills.